Assessment of the dental and skeletal effects of fan-type rapid maxillary expansion screw and Hyrax screw on craniofacial structures - Umarevathi Gopalakrishnan; Premkumar Sridhar (Wolters Kluwer Medknow Publications, 2017)
Aims and Objectives: The purpose of the study was to assess the skeletal and dental effects of fan-type rapid maxillary expansion (RME) appliance and Hyrax RME appliance on the craniofacial structures. Materials and Methods: The sample of the study included 12 patients with constricted maxillary arches. Acrylic bonded type of attachment was used for both groups. Changes in sagittal, vertical, and transverse relationship were assessed with lateral and frontal cephalograms, respectively. Intercanine and intermolar widths were measured with stone models. Pre- and immediate post-treatment records were statistically analyzed with Wilcoxon signed-rank test. The differences between the groups were evaluated using Mann-Whitney U-test. Since the data pertaining to intercanine width and intermolar width were normally distributed, parametric test of signifi cance (unpaired t-test) was used to compare them. Results: Results showed that Hyrax presented with signifi cantly greater increments for both nasal cavity width and maxillary width when compared to fan-type RME. Both groups had retroclination of incisors. The increase in the intercanine width was almost similar in both groups. Conclusion: Fan-type RME caused only minimal expansion of the intermolar width when compared to the Hyrax. The ratio between the intercanine and intermolar width expansion was nearly 4:1 in the fan-type RME and 0.75:1 in Hyrax.